2019
DOI: 10.1002/ece3.5806
|View full text |Cite|
|
Sign up to set email alerts
|

How phenotypic matching based on neutral mating cues enables speciation in locally adapted populations

Abstract: Maynard Smith's (American Naturalist, 1966, 100, 637) suggestion that in some cases a prerequisite for speciation is the existence of local ecological adaptations has not received much attention to date. Here, we test the hypothesis using a model like that of Maynard Smith but differing in the way animals disperse between niches. In previous studies, males disperse randomly between niches but females stay put in their natal niche. As a first step toward generalizing the model, we here analyze the case that equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…. Our results show quantitatively the balance required mechanism by which sexual imprinting is achieved, but results are nearly identical if offspring imprint on one of the parents, fathers, say, because this case differs from strict phenotype matching only for the case of DD offspring of CD X CD parents(Sibly et al, 2019).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…. Our results show quantitatively the balance required mechanism by which sexual imprinting is achieved, but results are nearly identical if offspring imprint on one of the parents, fathers, say, because this case differs from strict phenotype matching only for the case of DD offspring of CD X CD parents(Sibly et al, 2019).…”
mentioning
confidence: 67%
“…To see if, given a suitable mechanism for phenotype matching, local adaptation leads to speciation if a new neutral mating trait arises by mutation, we ran computer simulations of a model developed from Sibly et al (2019) and applied it to the cases of local adaptation shown in Figure 2. In the model of Sibly et al (2019), one of the local adaptation alleles is dominant to the other, but now we need to accommodate intermediate dominance as shown in Table 1.…”
Section: Section 2 Local Adaptation Leads To Speciation If a New Neut...mentioning
confidence: 99%
See 3 more Smart Citations